The relationship between family support and hemodialysis compliance in chronic kidney failure patients - Hidayati, Aribudiati Sri; Handani, Adinda Mayada Putri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Chronic kidney failure is a condition in which the kidneys experience a progressive decline in function. Chronic kidney failure sufferers in Yogyakarta are ranked 17th out of 25 provinces, reaching 66,433 patients. Family support is an important factor in the success of compliance with hemodialysis. Purpose: To determine the relationship between family support and hemodialysis compliance in chronic kidney failure patients at PKU Muhammadiyah Hospital, Yogyakarta. Method: The design of this study was quantitative with a cross-sectional design method. The sampling technique in this study used purposive sampling with a total of 74 respondents. The instruments used were the family support questionnaire and The End Renal Disease Adherence Questionnaire (ESRD-AQ) which had been modified by (Kim et al., 2010) and translated by (Syamsiah, 2011). Results: The data obtained showed good family support for 65 respondents (87.8%) and compliant compliance for 71 respondents (95.9%) and the sig value result was 0.000 <0.5. And the correlation that occurred was in the strong category with a result of 0.602. Conclusion: There is a significant relationship between family support and hemodialysis compliance in chronic kidney failure patients at PKU Muhammadiyah Hospital, Yogyakarta.   Keywords: Compliance; Family Support; Hemodialysis.